Strengthening Land Administration Governance Through Electronic Land Certificates for Bureaucratic Reform at The Medan City Land Office - Enos Bonar Hasudungan Lumban Tobing; Fitri Rafianti; Dahlan Dahlan (Journal of Research in Social Science and Humanities, 2025)
The implementation of land administration reforms through electronic land certificates presents a critical challenge in bridging the gap between normative legal frameworks and factual bureaucratic practice in Indonesia. This thesis examines the strengthening of land administration governance through electronic land certification at the Medan Land Office, with particular emphasis on its implications for bureaucratic reform. Employing socio-legal research methodology through qualitative inquiry, the study identifies a significant phenomenon termed "service duality," wherein public-facing service infrastructure appears modernised whilst backend data processing remains labour-intensive and manual-dependent. The research utilises a triadic analytical framework encompassing Radbruch's legal certainty theory, Soekanto's law effectiveness theory, and modernisation theory to analyse the disjuncture between law in books and law in action. Findings reveal that the implementation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Regulation No. 3 of 2023 on Electronic Documents encounters substantial technical, organisational, and sociological impediments, including incomplete data validation, inter-agency coordination deficiencies, and persistent public skepticism regarding digital documentation. The thesis demonstrates that successful land administration digitalisation necessitates not merely technological substitution of physical certificates, but rather systemic transformation encompassing data integrity assurance, inter-sectoral institutional integration, and cultural-cognitive acceptance. The study proposes four strategic interventions: procedural digitalisation reform, establishment of a unified data reconciliation unit, cybersecurity fortification with blockchain adoption, and humanistic socialisation combined with fiscal incentives. These recommendations are calibrated to achieve substantive bureaucratic reform that delivers not only administrative efficiency but also equitable access to justice and enhanced investment certainty across Medan